The integration of mapwork and environmental issues using local context in FET Geography: an investigation of current pedagogic practices to inform professional development - Batyi, Kekeletso Rejoyce (Rhodes University, Faculty of Education, Department of Education, 2012)
This is an interpretative case study of four Grahamstown Education District Further Education and Training (FET) schools. The study sets out to investigate how Geography teachers integrate mapwork and environmental issues using local context, with the intention of providing insights for future professional development. Data for this study were generated using qualitative methods such as document analysis, semi-structured interviews and lesson observations. Interviews were conducted with geography teachers, the subject advisor and a workshop facilitator. The evidence generated in the study revealed that contrary to the integrative design of the curriculum, there is a superficial integration of mapwork and environmental issues as well as a cursory reference to and use of local context. This was noted in both professional development support workshops and classroom practice. The study finds that efforts to improve performance in geography need to pay closer attention to curriculum policy that calls for an integration and localization of knowledge and skills for coherence and relevance. It also notes that there is a need for a focus on real-world problem solving in social, economic, cultural and physical environments through the use of inquiry-based local fieldwork. Local investigations provide an integrative space for content and skills as well as being an important point of reference from which learners can compare and contrast issues in other places such as provincial, national, continental, and global locations. A professional development programme that emphasizes integration and contextualization alongside the current focus on basic skills training is proposed to improve what teachers are delivering in the classroom and to support enquiry-based fieldwork and research to strengthen a place-based relevance in local, national and international contexts. Finally an exemplar for professional development is briefly developed for the topic of soil erosion.
Keywords: Geography -- South Africa -- Grahamstown -- Study and teaching (Secondary); Maps -- Study and teaching (Secondary) -- South Africa -- Grahamstown; Environmental education -- Study and teaching (Secondary) -- South Africa -- Grahamstown; Teachers -- Training of -- South Africa -- Grahamstown